Digital Renewal of University Education: Barriers, Opportunities, and Contributions to Sustainable Development Goals (SDGs) - Shaojie Ding; Olena Pavliuk; Tetiana Lysenko; Liudmyla Hetmanenko; Serhii Khrapatyi (ASEAN Journal of Educational Research and Technology, 2027)
The digital transformation of higher education creates opportunities and challenges, particularly in crisis-affected countries such as Ukraine. This study examines the effectiveness of digital educational technologies and their contribution to sustainable higher education. The study combined a literature-based analysis with a three-month pedagogical experiment involving 64 university students. The findings highlight the potential of online platforms, blended learning, artificial intelligence, gamification, and immersive technologies to support motivation, learning outcomes, personalization, and inclusiveness in higher education. However, limited digital competence, unequal infrastructure, insufficient funding, cybersecurity risks, and fragmented strategies remain barriers. The study proposes an integrated digital renewal framework combining technological, organizational, and pedagogical dimensions. This framework primarily supports sustainable development goals through innovation, inclusion, resilience, and partnerships.